Current issues in offender assessment and rehabilitation in Japan - Takahashi, Masaru (Approaches to offender rehabilitation in Asian jurisdictions, 2024)
Japan has one of the lowest crime rates in the world. Additionally, the number of crimes has been steadily decreasing in recent years. As new crimes are decelerating, the focus has shifted to assessing and treating those who repeatedly offend. Lately, the Japanese government has sought to strengthen cooperation among national and local governments and private sector partners to provide long-lasting support for reintegrating people released from prison. This chapter discusses recent advances in assessment and treatment practices for people who have offended in Japan. It also examines whether there is evidence for these approaches in preventing recidivism.